Effectiveness of Health Education on Stunting in Adolescents to Improve Children's Quality of Life in the Future (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Stunting is currently still a major nutritional health problem for toddlers in the world, this is proven by the still high stunting rate in the world, including in Indonesia and West Java. One of the efforts to prevent stunting is through education to direct or change adolescent behavior so that they are willing and able to improve their health and meet their nutritional needs.This community service aims to increase adolescent knowledge about stunting. The method used in this community service is health education through lectures, questions, and answers about preventing stunting. This health education activity was attended by 30 junior high school students as participants. The activity began with a pre-test, then the material was delivered using PowerPoint media, and questions and answers. To determine the effectiveness of health education activities on participants' knowledge about stunting prevention, a post-test was then conducted. To determine the effectiveness of health education activities on participants' knowledge about stunting, a pre-test and post-test were conducted. There was an increase in participants' knowledge about stunting after health education. It is hoped that schools will integrate material about stunting into Health Effort program. Cooperation is needed between teachers, health workers, and parents in providing ongoing information, and health workers can develop interesting and age-appropriate educational modules or media so that information about stunting is easier for students to understand and can be applied in everyday life.